Gut Microbiome Changes in Patients With Idiopathic Normal Pressure Hydrocephalus - Brandt, Emilia (Lippincott, 2025)
Background: The gut microbiome is a complex system within the human gastrointestinal tract. The bacteria play a significant role in human health, and some can promote inflammation and pathologic processes through chemical interactions or metabolites. Gut microbiome dysbiosis has been linked to some neurological and other diseases. Here we aimed to examine microbiome differences between patients with a progressive neurological disorder, idiopathic normal pressure hydrocephalus (iNPH), compared with healthy controls (CO).
Methods: We recruited 37 neurologically healthy CO and 10 patients with shunted iNPH. We evaluated these participants' cognition using the CERAD-NB test battery and CDR test, and collected a variety of information, including about dietary habits and health. We also collected fecal samples, which were subjected to 16S amplicon sequencing to analyze differences in gut microbiome composition.
Results: We found that the iNPH group exhibited significantly different abundances of 10 bacterial genera compared with the CO group. The Escherichia/Shigella and Anaeromassilibacillus genera were most remarkably increased. Other increased genera were Butyrivibrio, Duncaniella, and an unidentified genus. The decreased genera were Agathobaculum, Paramuribaculum, Catenibacterium, and 2 unidentified genera.
Conclusions: Here we report the first identified microbiome differences in iNPH patients compared with healthy controls.